Investigation of Synthesis of Sodium Aminodiborane in One Step and Its Reaction Kinetics - Meryem Sena Akkus; Goksel Ozkan (Molekul, 2020)
In this study, sodium aminodiborane (NaNH2(BH3)2) synthesis was carried out in a constant volume batch reactor with a single feed at various temperatures and inlet molar ratios. It was synthesized, ammonia borane and sodium hydride as precursors, by a wet chemical reaction method using tetrahydrofuran which is a solvent under atmospheric pressure. These experiments were carried out at varied temperature ranges from 0 °C to 24 °C, and varied inlet molar ratios (AB/NaH) from 0.75 to 1.25. Sodium amidoborane is synthesized when the experiment is carried out in a stoichiometric ratio, but sodium aminodiborane is synthesized when the mole of ammonia borane is higher than the mole of sodium hydride. In order to characterize the products, FTIR, XRD, GC-MS/MS, and quantitative analysis techniques were utilized. In addition, sodium aminodiborane’s synthesis reaction kinetic was determined. r apparent = 0.8594 e ^ (- 4366 / RT) C AB ^ (0.8) C NaH ^ (0.2). The apparent activation energy, Ea, and frequency constant, k0, were calculated about 4366 J/mol and 0.8594 h-1, respectively